Handdrawing techniques for architectural drawings by first-year students - Kendzierawska, Marta; Perepelytsia, Sofiia (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2023)
This article presents the results of a study conducted among first-year students attending the Fundamentals of Design – Architectural Composition class at the Architecture Department of the Faculty of Architecture, Building and Architecture department, Lublin University of Technology. The scope of the questionnaires included a selection of techniques used to create drawing works, as well as the opportunities for introducing new drawing tools and their influence on the final effect of works created during the classes.